OBTAINING BACTERIOPHAGES AND APPLICATION IN VETERINARY - Nifontova, B.B.; Chugunova, E.O. (Perm Federal Research Centre Journal, 2015)
The article shows the process of extracting bacteriophages from pathological material, obtaining bacteriophages drug and using phagotherapy for therapy of purulent otitis in dogs. It is known that there are antibiotic-resistant strains of microorganisms and bacteriophages can be an alternative source of antibacterial means of therapy. A cocker spaniel having purulent otitis served as the object of our research. Standard treatment directed at suppression of pathogenic microflora didn’t show any results, the microflora of purulent effluent in vitro was not sensitive to antibiotics. Purulent effluent was collected aseptically, and after indication and identification of its microflora, then we allocated Staphylococcus and Proteus bacteriophages from this pathological material. At the next stage of research we determined sensitivity and specificity of bacteriophages to the corresponding microflora, and also bacteriophages titer using Appelman and Gratsia method. After laboratory testing of phagolysate, phagotherapy was applied to purulent otitis and showed therapeutic effect within three days.